PELAYANAN MASJID KOTA (Masjid Sigi Lamo Kesultanan Ternate) - Abdul Rahman Arsyad (EDUCANDUM, 2018)
This study aims to identify and describe the forms of service and influence ofthe Sigi Mosque Lamo in improving religious and social activities of thecommunity.. The research problem, how is the form of service and supportingand inhibiting factors in city mosque activities. The approach used isqualitative descriptive methods. The results showed that the implementation ofreligion and religious coaching dominant was carried out in the Mosque of theSultanate of Sigi Lamo by using customary management of the sultanate.Service of Worship, preach and religious education through Fardh Prayers,Friday and Islamic holidays. Women cannot join prayer in congregation withmen, men are not allowed to use sarongs, must be long pants and wear cap /skullcap, and the limited Khatib and Imam who can lead and preach in themosque of the sultanate, all of which must be through the inauguration of theSultan. Supporting factors, the managers are enthusiastic in managing theprocession of activities and have a high concern and are obedient to thesultan's policies. Inhibiting factors, management and operational factorsmanually, the limited da'i. There is a need for collaboration between themosque management and the government (Ministry of Religion) and thecommunity about the development of da'wah. The sultanate may be able to givespace to all the sultanate mosques in the fulfillment Khatib without anylimitations.